2013
DOI: 10.4028/www.scientific.net/amm.465-466.1075
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Tools Design when Helical Milling on Carbon Fiber Reinforced Plastics (CFRP) Aluminum (Al) Stack

Abstract: Abstract. Hole making process is not strictly to the drilling technique where others machining could also influence to the quality in CFRP hole.Therefore, helical milling process becomes as an alternative method to produces bore on CFRP plate thus minimizing the defects. The common defects on CFRP are delamination, splintering and cracking. Meanwhile, if the CFRP stacking together with aluminum plate, burr at exit hole of aluminium plate is produced. Therefore, it is essential to control the critical machining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This result is in agreement with results in the literature [33]. This is due to the higher hardness of the aluminum panel (250 HV) compared to the carbon composites panel (180 HV) [34], resulting in lower impact on the fiber while drilling CFRP [35]. The thrust force of CFRP obtained from this experiment ranges from 87.69 N to 126.18 N, whereas for Al7075-T6, it varies between 218.21 N and 375.54 N. From the obtained result, R2 has the lowest CFRP peak thrust force, while R7 generates the lowest Al7075-T6's peak thrust force value.…”
Section: Thrust Force Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with results in the literature [33]. This is due to the higher hardness of the aluminum panel (250 HV) compared to the carbon composites panel (180 HV) [34], resulting in lower impact on the fiber while drilling CFRP [35]. The thrust force of CFRP obtained from this experiment ranges from 87.69 N to 126.18 N, whereas for Al7075-T6, it varies between 218.21 N and 375.54 N. From the obtained result, R2 has the lowest CFRP peak thrust force, while R7 generates the lowest Al7075-T6's peak thrust force value.…”
Section: Thrust Force Analysissupporting
confidence: 92%
“…The average surface roughness (Ra) was used as a measurement parameter in this study. In general, the acceptable surface roughness is an Ra value of CFRP and Al7075-T6 below 3 µm and 1 µm, respectively [35]. The hole surface roughness for both CFRP and Al7075-T6 for both runs are presented in Figure 6.…”
Section: Hole Surface Roughness Analysismentioning
confidence: 92%
“…It was reported that hole quality defects caused by the drilling process, such as hole diameter errors, entry/exit delamination, and fiber-pull outs/tearing out, have been responsible for rejecting almost 60% of the composite parts in production. 15,16 Generally, hole quality from fiber reinforced plastics (FRP) drilling is influenced by multiple factors, such as drill type/geometry, fiber/resin properties, process conditions, and cutting forces/vibrations. Many studies focus on the formation mechanisms of delamination, varied by the drilling process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that hole quality defects caused by the drilling process, such as hole diameter errors, entry/exit delamination, and fiber-pull outs/tearing out, have been responsible for rejecting almost 60% of the composite parts in production. 15 , 16…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibre reinforced plastics (CFRP) and Fibre metal laminates (FMLs)are often used in various applications of aircraft components and structures due to their high mechanical properties material. Both of thesesuperior substitutes materials are widely adoptedwhen compared to conventional materials required in lighter structural aircrafts; thereby improving fuel efficiency but still retaining the integrity of the structure.The poor surface quality, geometry defects and work piece damage thatare normally found in metalsmay cause the long-term performance of this kind of materialsto be degraded [1] [2]. Aluminium grade 2024 and 7075 are normally used as a core or skinmaterial of FMLs due to malleability and have excellent machinability compared to carbon fibers itself.…”
Section: Introductionmentioning
confidence: 99%